Carbon Dioxide and n‐Hexane Absorption Using a Gas‐Liquid‐Liquid Reactor. Issue 4 (3rd February 2016) - Gómez‐Díaz, Diego; López‐Rivas, David; Navaza, José M.; Couvert, Annabelle
Abstract: Simultaneous absorption of the acid gas CO2 and a volatile organic compound (VOC; here n ‐hexane) from a polluted gas stream by using an emulsion in a gas‐liquid‐liquid (GLL) reactor was investigated. In order to enhance the VOC capture, a nonaqueous liquid phase in the form of silicone oil was applied in the gas absorber. In addition, the regeneration process of both liquid phases was analyzed. The effect of methyldiethanolamine concentration in the aqueous phase and percentage of the organic phase was evaluated, showing opposite results for the liquid phases regarding each gas due to the differences between them. A higher amount of silicone oil causes a significant improvement in VOC absorption rate with negligible influence on CO2 behavior. The gas composition was modified by nitrogen. Abstract : Several gas‐liquid‐liquid systems were used in order to increase the effectiveness of gas absorption treatment for acid gas and volatile organic compound streams. Simultaneous absorption of CO2 and n ‐hexane from a polluted gas stream was achieved by using an emulsion in a gas‐liquid‐liquid reactor. Both liquid phases were regenerated by increasing the temperature to remove each gas component.